2019
DOI: 10.1159/000501720
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Decreases Regulatory T Cell Number in Mice by Reducing IL-2 Secretion

Abstract: <b><i>Background:</i></b> Ouabain (OUA) is a cardiotonic glycoside originally extracted from African plants. It has also been described as an endogenous component in mammals, being released in stress situations mainly by the adrenal gland. OUA has been reported to be capable of inhibiting mitogen-induced lymphocyte proliferation and also affects B and T lymphocytes. <b><i>Objectives:</i></b> The aim of this work is to show the effects of OUA in peripheral T lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The results of the Annexin V/PI investigation suggest that the majority of SK-BR-3 cells treated with cardiotonic glycosides do not undergo a process of necrosis, but die by apoptosis. These results support the data obtained by Da Silva et al [ 26 ] on murine Tregs lymphocytes, by Chang et al [ 10 ] on DU-145 cells, and Khajah et al [ 11 ] on triple-negative breast cancer cells. At micromolar concentrations, the most likely mechanism of ouabain-induced programmed cell death is due to energy substrate depletion.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the Annexin V/PI investigation suggest that the majority of SK-BR-3 cells treated with cardiotonic glycosides do not undergo a process of necrosis, but die by apoptosis. These results support the data obtained by Da Silva et al [ 26 ] on murine Tregs lymphocytes, by Chang et al [ 10 ] on DU-145 cells, and Khajah et al [ 11 ] on triple-negative breast cancer cells. At micromolar concentrations, the most likely mechanism of ouabain-induced programmed cell death is due to energy substrate depletion.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, digoxin decreased the number of Th17 cells and increased the number of T-Regs, which promoted immunosuppression in mice [109]. Ouabain has been shown to reduce the number of T-regs by decreasing Il-2 production by T lymphocytes [107]. The regulation of lymphocytes by CTS will offer new and modified treatment strategies for rheumatologic and autonomic diseases such as Chagrin syndrome [90], rheumatoid arthritis [109] via promoting T-Regs and suppressing joint inflammation and bone erosion in mice CIA (collagen induced arthritis) arthritis model.…”
Section: Regulatory T-cellsmentioning
confidence: 99%
“…Telocinobufagin has also been shown to dramatically enhance the proliferative response of splenocytes to concanavalin A, ovalbumin and substantially increase transcription factors T-bet (Th1) mRNA level and the CD3(+)/CD3(+)CD4(+)/CD3(+)CD8(+) phenotype in splenocytes from ovalbumin-immunized mice [106]. There are contradictory data on the effect of ouabain on the number of T-helpers cells, for example, in a study [107] it was shown that intraperitoneal injection of ouabain in mice significantly decreased the number of CD4+ T-lymphocytes in the spleen, especially regulatory T-cells, while the percentage and total number of lymphocytes in mesenteric lymph nodes remained the same [108]. Reduction of levels of antigen-specific T-helper lymphocytes cytokines (IL-4, IL-5, IL-13) in bronchoalveolar lavage fluid by bufalin was described above [104].…”
Section: T-helpersmentioning
confidence: 99%
“…Besides, ouabain suppressed human renal cancer OS-RC-2 cell proliferation by targeting to the NKA α3 isoform (32). Furthermore, ouabain reduced IL-2 secretion and resulted in a decrease in regulatory T cell numbers in mice (33).…”
mentioning
confidence: 98%